Enhanced Peak and Extended Cooling of the Extreme-ultraviolet Late Phase in a Confined Solar Flare - Shihan Li; Yu Dai; Mingde Ding; Zhen Li; Jinhan Guo; Hao Wu (The Astrophysical Journal)
We present observations and analysis of an X1.8 noneruptive solar flare on 2012 October 23, which is characterized by an extremely large late-phase peak seen in the warm coronal extreme-ultraviolet (EUV) emissions (∼3 MK), with the peak intensity over 1.4 times that of the main flare peak. The flare is driven by a failed eruption of a magnetic flux rope, whose strong squeeze force acting on the overlying magnetic structures gives rise to an intense early heating of the late-phase loops. Based on differential emission measure analysis, it is found that the late-phase loops experience a “longer-than-expected” cooling, without the presence of any obvious additional heating, while their volume emission measure maintains a plateau for a long time before turning into an evident decay. Without the need for an additional heating, we propose that the special thermodynamic evolution of the late-phase loops revealed in this flare might arise from loop cross-sectional expansions with height, which are evidenced by both direct measurements from EUV images and by magnetic field extrapolation. By blocking the losses of both heat flux and mass from the corona, such an upward cross-sectional expansion not only elongates the loop-cooling time, but also more effectively sustains the loop density, therefore leading to a later-than-expected occurrence of the warm coronal late phase in combination with a sufficiently high late-phase peak. We further verify such a scenario by analytically solving the cooling process of a late-phase loop characterized by a variable cross section.